Computing k−Rank Answers with Ontological CP−Nets - Noia, T; Lukasiewicz, T; Martinez, M; Simari, G; Tifrea−Marciuska, O (DCS, 2014)
The tastes of a user can be represented in a natural way by using qualitative preferences. In this paper, we describe how to combine ontological knowledge with CP-Nets to represent preferences in a qualitative way and enriched with domain knowledge. Specifically, we focus on conjunctive query (CQ) answering under CP-net-based preferences. We define k-rank answers to CQs based on the user’s preferences encoded in an ontological CP-net and we provide an algorithm for k-rank answering CQs.